Tipologi Pertumbuhan Ekonomi Indonesia Dalam Perspektif Komunikasi Pembangunan Leo Klassen - Probo Sasongko; Erwin Setyawan; Teguh Hidayatul R Rachmad; Doan M. Y. H Sihombing (Brand Communication, 2023)
Economic growth in Indonesia is an inseparable part of the effort to improve and manage the nation's development. The government's efforts to revive development which places the main role on improving the regional economy are an important priority in bringing back the movement of the economy which was halted due to the Covid-19 storm that hit the Akita nation. Improvement in several vital sectors in each region is a strategic step to move the national economy back into motion later, therefore, cooperation based on overcoming acts of radicalism, extremism and terrorism is a shared manifestation of the Akita nation on how to present a government that runs well in optimizing the wheel the nation's economy.